System and method for processing a data subject rights request using biometric data matching - Durak, Fatma Betül; Gehrer, Stefan; Trieflinger, Sven; Zimmermann, Christian (2024)
A system and method are disclosed for processing data subject rights requests. The system and method advantageously enable data controllers to train machine learning models on unaltered data having PII, while maintaining the privacy of the unaltered data and enabling compliance with data subject rights requests with respect to the data. The system and method incorporate a biometric database that stores biometric data extracted from the unaltered data having PII. In order to identify data relating to a data subject rights request, biometric data is received from the data subject and is matched against the biometric data stored in the biometric database. Based on the matched biometric data, the original unaltered source data having PII can be identified for the purpose of exercising one or more data subject rights, such as erasure, access, and objection to processing.